ANALISIS PENERAPAN UPAH TENAGA KERJA DALAM PERSPEKTIF EKONOMI ISLAM (STUDI KASUS PADA PT. NUSANTARA SURYA SAKTI KOTA KENDARI) - Ridha Dwi Sendari; Gamsir Gamsir; Asrip Putera (Universitas Halu Oleo, 2022)
The purpose of this study is to determine the application of labor wages and to determine the Islamic economic view of the application of labor wages. This research was conducted in 3 branches of PT. Nusantara Solar Sakti. The data analysis method is a qualitative descriptive analysis. Source of data is primary data by direct interviews with informants. Researchers chose informants as many as 15 employees from 3 branches and 1 leader. The results of the study show that the application of labor wages has a work contract, namely working days, working hours, the amount of wages, and the division of labor or the form of work. Work contracts are submitted orally and in writing, the amount of wages given is in accordance with company regulations without any bargaining regarding the amount of wages, wages are paid at the end of the month, but not all employee wages are based on applicable regulations (UMP/UMK or UMSP/UMSK). Some of the remuneration practices implemented are not in accordance with Islamic economic principles. The work contract/agreement is in accordance with Islamic economic principles where there is a work agreement/contract that is notified before the worker starts working.